What is a child? : A comparative study on understanding the definition of a child when considering the child’s best interests principle in European family law and Islamic family law - Kalaja, Laura (My University, 2024)
This thesis seeks to enrich our knowledge on how the definition of a child is understood in European family law and Islamic family law. It also perceives the influence of this conception when considering the child’s best interests principle. The study begins by recognizing these two unique family law systems for the protection of children’s rights and continues by exploring how a child and child’s best interests is understood in these legal frameworks. Since both European and Islamic family laws reached to their current level of development through constant changes and both are facing a variety of dilemmas in defining and regulating the modern family, this thesis offers a valuable insight on how to navigate between the European family law and the Islamic family law for the benefit of a child. The understanding of the concept of a child can vary significantly across different cultures and societies, and it influences on how the child’s best interests is understood. The United Nations Convention on the Rights of the Child (1989) acknowledges the significance of cultural diversity as a right for children, but it also emphasizes the pursuit of a universal standard as an ideal. The child’s best interests principle should ensure and improve the equal well-being of children everywhere. Using comparative analysis, this thesis illustrates how the child’s best interests principle is implemented in respective legal frameworks, particularly within the context of custody matters. To understand the performative character of the concept of a child in a legal framework, regarding the concept of the child’s best interests principle, this study relies on conceptual analysis to examine the definitions, rights, and responsibilities to children within respective legal systems. To answer the main question at hand, a legal linguistic approach is needed in order to examine the concept of a child by considering how the term “child” is defined, interpreted, and applied. Furthermore, to explore whether there is a legal framework that fulfils its role more effectively than the other in discerning the best interests of a child, a functional approach is used as an evaluative standard. This analysis highlights problems in the realization of the best interests of a child equally between the sexes and equally between the dual frameworks of family law. It raises questions about the discriminatory grounds for defining the concept of a child. This thesis proposes that more careful harmonization of the concept of a child would improve the realization of the principle and children’s rights, and increase the equal well-being of children. The need for further research focuses on issues between European family law and Islamic family law, especially regarding the legal status of women and girls.

Tämän tutkielman tarkoitus on rikastuttaa tietämystämme siitä, miten lapsen määritelmä ymmärretään yhtäältä eurooppalaisessa perheoikeudessa ja toisaalta islamilaisessa perheoikeudessa, kun tarkastellaan lapsen edun periaatetta. Aluksi tunnistetaan nämä kaksi ainutlaatuista perheoikeudellista järjestelmää lasten oikeuksien suojelemiseksi ja sen jälkeen tarkastellaan, miten lapsi ja lapsen etu ymmärretään näissä oikeudellisissa kehyksissä. Sekä eurooppalainen että islamilainen perhelainsäädäntö ovat saavuttaneet nykyisen kehitystasonsa useiden muutosten myötä ja kohtaavat tälläkin hetkellä monia haasteita modernin perheen määrittelyssä ja sääntelyssä. Tutkimus selvittää, miten navigoida eurooppalaisen ja islamilaisen perheoikeuden välillä lapsen etua ajatellen. Lapsen käsitteen ymmärtäminen voi vaihdella merkittävästi eri kulttuureissa ja yhteiskunnissa ja se vaikuttaa myös siihen, miten lapsen etu ymmärretään. Yhdistyneiden kansakuntien (YK) lapsen oikeuksien yleissopimussopimus (1989) tunnustaa kulttuurisen monimuotoisuuden merkityksen lasten oikeutena, mutta korostaa myös universaalin standardin tavoittelua ihanteena. Lapsen edun periaatteen tulisi vahvistaa ja parantaa lasten tasa-arvoista hyvinvointia kaikkialla. Tutkielma havainnollistaa vertailevan analyysin avulla, miten lapsen edun periaatetta sovelletaan kyseisissä perheoikeudellisissa viitekehyksissä, erityisesti huoltajuuskysymyksissä. Ymmärtääksemme paremmin lapsen käsitteen performatiivista luonnetta sekä lapsen edun käsitettä oikeudellisessa kehyksessä, työssä nojaudutaan käsitteelliseen analyysiin tutkittaessa lapsen määrittelyä, oikeuksia sekä velvollisuuksia asianomaisissa oikeusjärjestelmissä. Päätutkimuskysymystä tarkastellaan oikeuslingvistisellä lähestymistavalla analysoiden, miten termi ”lapsi” määritellään, miten sitä tulkitaan ja sovelletaan. Lisäksi kun verrataan, onko olemassa perheoikeudellista kehystä, joka täyttää tehtävänsä vertailukohdettaan tehokkaammin lapsen edun huomioimisessa, käytetään funktionaalista lähestymistapaa arviointiperusteena. Analyysi tuo esiin ongelmia lapsen edun toteutumisessa tasa-arvoisesti sukupuolten välillä sekä yhdenvertaisesti eri perheoikeudellisten viitekehysten välillä. Johtopäätökset nostavat esiin näkökulman lapsen käsitteen määrittelyyn liittyvistä syrjivistä lähtökohdista. Tutkielma esittää, että lapsen käsitteen huolellisempi yhdenmukaistaminen parantaisi lapsen edun periaatteen ja lasten oikeuksien toteutumista sekä lisäisi lasten tasapuolista hyvinvointia. Jatkotutkimustarve kohdistuu eurooppalaisen ja islamilaisen perheoikeuden välisiin kysymyksiin, jotka liittyvät erityisesti naisten ja tyttöjen oikeudelliseen asemaan.
Keywords: Child, Child’s best interests, Children’s rights, Islamic family law, European family law, lapsi, lapsen etu, lapsen oikeudet, islamilainen perheoikeus, eurooppalainen perheoikeus